KEDUDUKAN PERJANJIAN BERSAMA (PB) TERHADAP PERJANJIAN KERJA BERSAMA (PKB) DALAM HUBUNGAN INDUSTRIAL - Muhammad Holy One N Singadimedja (Universitas Borneo Tarakan, 2019)
ABSTRAKLegally that the relationship between workers and employers are the same even though the socio-economic position between employees and employers is different, the nature of the employment law has resulted in employment relationships are not always harmonious between workers / unions and employers in industrial relations, the number of employers who eliminate or reduce workers' rights to conduct collective bargaining (PB) to deviate the collective Labour agreement (CLA), whereas in the company there has been a Labour agreement (CLA) is still valid by reason of the collective labor agreement (CLA), which is not in accordance with laws and regulations.The conclusion obtained is that the position of the Collective Agreement (PB) as a Source of Law Autonomous Employment Law is part of the Collective Labor Agreement for the duration of the validity of PKB there are things that do not fit in the employment relationship so it is possible made the Collective Agreement which will then be included in the change PKB with the provisions PB must be registered at the Industrial Relations court, the legal effect of the NT tertentangan with CLA, PB may be declared null and void, cancellation of PB can be done through the judicial land in the area of collective agreements made, since the Industrial Relations court has no competence to resolve disputes cancellation of the Collective Agreement. Keywords: Position, the Collective Agreement, Working Agreement